2010
DOI: 10.1590/s0074-02762010000400026
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early infection with Echinostoma paraensei on the interaction of Schistosoma mansoni with Biomphalaria glabrata and Biomphalaria tenagophila

Abstract: Infection caused by the trematode Echinostoma paraensei has been shown to interfere in the natural resistance to infection by Schistosoma mansoni. Biomphalaria glabrata is susceptible to infection, while Taim isolate Biomphalaria tenagophila is resistant to infection by S. mansoni. These two snail species were assessed for infection with E. paraensei two days after exposure to S. mansoni miracidia. The number of B. tenagophila and B. glabrata infected with E. paraensei was lower in co-infected group, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This also holds true for snails confronted with other non-schistosome pathogens. For example, Echinostoma paraensei has been shown to infect both R and S strains of B. glabrata ( 66 , 69 ), while bacterial pathogens Paenibacillus ( 70 ) and Vibrio parahaemolyticus ( 71 ) infect all exposed B. glabrata strains regardless of their schistosome-susceptibility status. This strongly suggests that the S and R phenotypes exhibited by these model B. glabrata/S.…”
Section: Resultsmentioning
confidence: 99%
“…This also holds true for snails confronted with other non-schistosome pathogens. For example, Echinostoma paraensei has been shown to infect both R and S strains of B. glabrata ( 66 , 69 ), while bacterial pathogens Paenibacillus ( 70 ) and Vibrio parahaemolyticus ( 71 ) infect all exposed B. glabrata strains regardless of their schistosome-susceptibility status. This strongly suggests that the S and R phenotypes exhibited by these model B. glabrata/S.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike what was expected, the results showed that these digeneans act in different ways to evade the host defense mechanisms (LAFFERTY;SHAW, 2013). Corroborating these data, Garcia et al (2010) showed that even with a prior infection by E. paraensei, B. tenagophila (TAIM) maintained refractoriness when exposed to S. mansoni. In fact, it has been shown that immune suppression (or interference) is a key function in the BiomphalariaEchinostoma relationship, allowing the parasite to evade attack of humoral factors such as FREPs (ADEMA et al, 2013).…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, different isolates of snail species can show a heterogeneous pattern to a parasite species infection (COELHO et al, 2004;ROSA et al, 2006;GARCIA et al, 2010;NACIF-PIMENTA et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Loker et al ., 1987 ; Nollen, 1996 ; Maldonado et al ., 2005 ), (ii) parasite interaction (in both intramolluscan and vertebrate phases) with Schistosoma mansoni Sambon, 1907 and/or other echinostomes (e.g. Sullivan and Richards, 1981 ; Combes, 1982 ; Maldonado et al ., 2001 b ; Garcia et al ., 2010 ; Hanington et al ., 2010 ), (iii) ultrastructural morphology of different developmental stages (e.g. Fujino et al ., 2000 ; Maldonado et al ., 2001 a ; Pinheiro et al ., 2005 ; Souza et al ., 2017 a ), (iv) biochemical and pathological changes associated with the infection in molluscs and rodents (e.g.…”
Section: Introductionmentioning
confidence: 99%